2021
DOI: 10.1590/0001-3765202120191368
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and molecular properties of Phenoxyacetic Acids Derived from Eugenol and Guaiacol compared to the herbicide 2,4-D

Abstract: Herbicides are agrochemicals applied in the control of weeds. With the frequent and repetitive use of these substances, serious problems have been reported.Compounds of natural origin and their derivatives are attractive options to obtain new compounds with herbicidal properties. By aiming to develop compounds with potentiated herbicidal activity, phenoxyacetic acids were synthesized from eugenol and guaiacol. The synthesized compounds were characterized and the herbicidal potential of phenoxyacetic acids and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…This relationship was observed in this study, as the esters 3, 4, and 5, derived from eugenol, carvacrol, and guaiacol, respectively, showed an increase in both the MI and the CA rate. The increase in the MI was also observed in L. sativa treated with eugenoxyacetic acid 30 .…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…This relationship was observed in this study, as the esters 3, 4, and 5, derived from eugenol, carvacrol, and guaiacol, respectively, showed an increase in both the MI and the CA rate. The increase in the MI was also observed in L. sativa treated with eugenoxyacetic acid 30 .…”
Section: Resultsmentioning
confidence: 58%
“…Cell death may explain the reduction in growth of roots and aerial part of L. sativa and S. bicolor seedlings exposed to esters 1, 3, and 5 58 . Alves et al 30 found a 5-fold increase in the rate of adherent chromosomes in cells treated with eugenol and eugenoxyacetic acid.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations